2010
DOI: 10.1590/s2236-89062010000100001
|View full text |Cite
|
Sign up to set email alerts
|

Epífitas vasculares: histórico, participação taxonómica e aspectos relevantes, com ênfase na Mata Atlântica

Abstract: O Dossel é um ecossistema complexo e ecologicamente diverso, possuindo espécies, nichos e processos próprios. Dentre as diversas formas de vida que o compõem, destaca-se a epífita. Este trabalho procurou reunir informações sobre esta sinúsia estabelecendo padrões florísticos para as epífitas no bioma Mata Atlântica. A maioria das epífitas é monocotiledônea (63,5%), seguida das Monilophyta (16,4%), Eudicotiledôneas (14,1%), Magnoliídeas (4,5%) e Lycophyta (1,6%). As famílias mais ricas são Orchidaceae com 45,8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
4
40

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 80 publications
14
70
4
40
Order By: Relevance
“…In the subtropical forests of Brazil, Orchidacae is also cited as the most diverse family (Alves et al 2008;Neto et al 2009;Kersten 2010;Blum et al 2011). However, despite not having the highest species richness in the present study, Orchidacae showed the most generic diversity.…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…In the subtropical forests of Brazil, Orchidacae is also cited as the most diverse family (Alves et al 2008;Neto et al 2009;Kersten 2010;Blum et al 2011). However, despite not having the highest species richness in the present study, Orchidacae showed the most generic diversity.…”
Section: Resultscontrasting
confidence: 49%
“…On the other hand, the family was not even recorded in studies in a terra firme forest in the Brazilian state of Pará (Pos & Sleegers 2010), nor in a savanna in Humaitá, Brazil (Gottsberger & Morawetz 1993). The high occurence of Bromeliaceae in surveys of the epiphytic community is expected for the Atlantic forest, as this is one of the main centers of diversity of this family ), where Bromeliaceae is often cited as the second most diverse (Kersten 2010). In the Brazilian Amazon, the bromeliads are found more frequently in floodplains (baixios), low whitesand forests (campinas), high whitesand forests (campinaranas) and seasonally blackwater-flooded Amazon forests (igapó) (Sousa & Wanderley 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O número de epífitas pode ser comparado ao encontrado em áreas de Floresta Ombrófila Densa (Labiak & Prado 1998, Matos et al 2010) e pode ser explicado pelas condições microclimáticas do PEG, especialmente nas florestas de galerias, onde a umidade relativa do ar é notavelmente mais elevada e constante, quando comparada com outras formações florestais do Parque, condições que providenciam ambientes propícios ao epifitismo (Kersten 2010). Desta forma, com os dados atualmente disponíveis, as samambaias e licófitas representam 42% das epífitas vasculares registradas no Parque.…”
Section: Villosa)unclassified
“…Cactaceae family comprises 124 genera and 1,438 species (Hunt et al, 2006) primarily presenting neotropical distribution (Taylor, 1997). The group has countless adaptations to the arid conditions, however, approximately 15% of its representatives, about 220 species, are adapted to the epiphytic behavior in humid tropical and subtropical forests (Bauer, 2006), standing out among the 20 families with the greatest number of epiphytes (Kersten, 2010).…”
Section: Introductionmentioning
confidence: 99%